Metabolic Syndrome and Breast Cancer Risk - Wani, Burhan; Aziz, Shiekh Aejaz; Ganaie, Mohammad Ashraf; Mir, Mohammad Hussain (Indian Journal of Medical and Paediatric Oncology, 2017)
Objective: The study was meant to estimate the prevalence of metabolic syndrome in patients with breast cancer and to establish its role as an independent risk factor on occurrence of breast cancer. Materials and Methods: Fifty women aged between 40 and 80 years with breast cancer and fifty controls of similar age were assessed for metabolic syndrome prevalence and breast cancer risk factors, including age at menarche, reproductive status, live births, breastfeeding, and family history of breast cancer, age at diagnosis of breast cancer, body mass index, and metabolic syndrome parameters. Results: Metabolic syndrome prevalence was found in 40.0% of breast cancer patients, and 18.0% of those in control group (P = 0.02). An independent and positive association was seen between metabolic syndrome and breast cancer risk (odds ratio = 3.037; 95% confidence interval 1.214–7.597). Conclusions: Metabolic syndrome is more prevalent in breast cancer patients and is an independent risk factor for breast cancer.
Keywords: Breast cancer; metabolic syndrome; risk factor